Connectional subdivision of the claustrum: two visuotopic subdivisions in the macaque - Gattass, Ricardo; Soares, Juliana G. M.; Desimone, Robert; Ungerleider, Leslie G. (Frontiers in Systems Neuroscience, 2014)
The claustrum is a surprisingly large, sheet-like neuronal structure hidden beneath the inner surface of the neocortex. We found that the portions of the claustrum connected with V4 appear to overlap considerably with those portions connected with other cortical visual areas, including V1, V2, MT, MST and FST, TEO and TE. We found extensive reciprocal connections between V4 and the ventral portion of the claustrum (vCl), which extended through at least half of the rostrocaudal extent of the structure. Additionally, in approximately 75% of the cases, we found reciprocal connections between V4 and a more restricted region located farther dorsal, near the middle of the structure (mCl). Both vCl and mCl appear to have at least a crude topographic organization. Based on the projection of these claustrum subdivisions to the amygdala, we propose that vCl and mCl are gateways for the transmission of visual information to the memory system. In addition to these crude visuotopically organized regions, there are other parts of the claustrum that obey the topographical proximity principle, with considerable overlap of their connections. There is only an overall segregation of claustrum regions reciprocally connected to the occipital, parietal, temporal and frontal lobes. The portion of the claustrum connected to the visual cortex is located ventral and posterior; the one connected to the auditory cortex is located dorsal and posterior; the one connected to the somatosensory cortex is located dorsal and medial; the one connected to the frontal premotor and motor cortices is located dorsal and anterior; while the one connected to the temporal cortex is located ventral and anterior. The extensive reciprocal connections of the claustrum with almost the entire neocortex and its projections to the hippocampus, amygdala and basal ganglia prompt us to propose its role as a gateway for perceptual information to the memory system.